2016
DOI: 10.1097/ccm.0000000000001354
|View full text |Cite
|
Sign up to set email alerts
|

Organ System Network Disruption in Nonsurvivors of Critically Ill Patients

Abstract: This study, as a preliminary proof-of-concept, quantitatively demonstrated a more disrupted network structure of organ systems in the nonsurvivors compared with that in the survivors. These observations suggest the necessity of assessment for organ system interactions to evaluate critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…These findings support the hypothesis that decreased organ system interaction is associated with poor prognosis in chronic liver failure. Our findings also continue to support previous studies suggesting that systemic dysfunction in acute life-threatening pathophysiology with multisystem involvement is attributed to a loss of homeostatic interorgan connectivity ( Buchman, 2002 ; Chovatiya and Medzhitov, 2014 ), most notably in the recent studies published by Asada et al (2016 , 2019) . Although our study explores multisystem disease of a chronic nature, the characteristics associated with poor prognosis in non-survivors remain similar, namely the breakdown of organ system connectivity, loss of homeostatic stability and isolation of individual organ system clusters.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings support the hypothesis that decreased organ system interaction is associated with poor prognosis in chronic liver failure. Our findings also continue to support previous studies suggesting that systemic dysfunction in acute life-threatening pathophysiology with multisystem involvement is attributed to a loss of homeostatic interorgan connectivity ( Buchman, 2002 ; Chovatiya and Medzhitov, 2014 ), most notably in the recent studies published by Asada et al (2016 , 2019) . Although our study explores multisystem disease of a chronic nature, the characteristics associated with poor prognosis in non-survivors remain similar, namely the breakdown of organ system connectivity, loss of homeostatic stability and isolation of individual organ system clusters.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Asada et al (2016) reported the first clinical application of network analysis to evaluate interorgan relationships between critically ill surviving and non-surviving patients with multiple organ failure. They challenged the reliability of conventional scoring methods, which sum up degrees of individual organ dysfunction to represent systemic illness pathophysiology and disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…This study is a subanalysis of our prospective observational studies [ 24 – 26 ]. The cohort in this study was selected from these previous prospective observational studies conducted in the medical–surgical mixed ICU at the University of Tokyo Hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Future investigation can pave the way to understand the mechanism of these effects by using an electrophysiologic (direct vagus nerve recording) or pharmacologic approach. Development of new analytical methods in Network Physiology will also help to uncover the mechanism of multiple organ failure in cirrhosis form a different perspective (Bartsch et al 2015, Xiong et al 2017, Asada et al 2016, Ivanov et al 2016, Kanter et al 2015. For example, multiscale network construction (Shashikumar et al 2017) can be employed for quantification of cardiovascular and respiratory interaction within the context of sepsis in patients with liver failure.…”
Section: Discussionmentioning
confidence: 99%